Relaxation processes on intersurface of bioglass composite materials - Wójcik, Agata; Szarska, Stanisława (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The basic problems one encounters when designing materials for medical applications are biocompatibility and mechanical properties. Recently, a development in the technology of composite materials has been observed. Bioactive glasses are used as a coating on porous corundum (good mechanical properties) implant materials. The technique used for producing glass components involves chemical routes, by the sol–gel process. The effect of a physiological solution on the surface properties of bioglasses and composites slightly differing in their chemical compositions has been examined by dielectric spectroscopy and DTA method. The temperature dependence of conductivity has been measured many times during the reduction and annealing processes, i.e., at various reduction and relaxation stages. The layer formation and the type of electrical charge on the surface of an implant plays a significant role in the generation and remodeling of a bone tissue. Moreover, our measurements allow to preliminary identify the transport mechanism in the considered material.
Optica Applicata, Vol. 38, 2008, nr 1, s. 267-276
Keywords: optyka; bioglass; biocomposite; dielectric spectroscopy; DTA